AMPEROMETRIC DETERMINATION OF RHENIUM IN DIFFERENT OBJECTS BY SOME ORGANIC BASIC DYES. CALCULATION OF SOLUBILITY PRODUCTS FOR OBTAINING INSOLUBLE COMPOUNDS (Proceedings of the YSU B: Chemical and Biological Sciences, 2004)
Possibility of rhenium determination in different rhenium-containing objects by amperometric titration method using some organic basic dyes as analytical reagents (Rhodamine G, Rhodamine 6G, Safranine T) has been shown. Titrations have been carried out in 0.8–1.0 M phosphoric acid medium on the platinum indicating microelectrode at +l.4 V (Rhodamine G, Rhodamine 6G) and 0.0 V (Safranine T) potentials. Solubility products values for compounds forming during interaction between perrhenate-ions and cations of the mentioned organic basic dyes (as well as Crystal Violet and Methyl Violet) have been calculated by means of two independent methods (photometric and gravimetric).
Keywords: rhenium determination; amperometric titration method; phosphoric acid medium; organic basic dyes